A case of male perineal aggressive angiomyxoma with expressions of female hormone receptors. Issue 4 (13th May 2022) - Hisano, Mizuki; Matsuura, Tomohiko; Kato, Renpei; Maekawa, Shigekatsu; Kato, Yoichiro; Kanehira, Mitsugu; Suzuki, Masamichi; Nakayama, Manabu; Takata, Ryo; Obara, Wataru
Abstract : Introduction: Aggressive angiomyxoma is a rare mesenchymal tumor in females of reproductive age that occurs in the pelvis and perineal zone with a high risk of local infiltration and recurrence. Male aggressive angiomyxoma in perineal zone is very rare. Case presentation: A 63‐year old male presented to our hospital with chief complaint of perineal mass. He was diagnosed with perineal lipoma by needle biopsy 3 years before. Computed tomography revealed a 16 cm perineal tumor without lymph node or distal metastasis. As the tumor had gradually increased, we performed tumor resection. The histological diagnosis of tumor using immunohistochemistry was aggressive angiomyxoma with complete resection. Moreover, expressions of both estrogen and progesterone receptors were recognized. No recurrence was seen 9 months after surgery. Conclusion: Male aggressive angiomyxoma is a very rare tumor, which has expressions of female hormone receptors. Hormonal therapy might be effective for perioperative therapy or recurrence.